Chemoenzymatic Synthesis of Nitrogen Polymers with Biomedical Applications Catalyzed by Lipases - Baldessari, Alicia; Garcia Liñares, Guadalupe Eugenia
The application of Candida antarctica lipase B as catalyst in the synthesis of two examples of nitrogen polymers is described. Firstly, we report anovel linear polyamidoamine oligomer, obtained by polymerization of ethyl acrylate and N-methyl-1,3-diaminopropane, catalyzed by Candida antarctica lipase B immobilized on polypropylene. The second part of the chapter describes an efficient route for the synthesis of a novel β-peptoid oligomer with hydroxyalkyl pendant groups in the nitrogen atom, through the polymerization of ethyl N-(2-hydroxyethyl)-β-alaninate catalyzed by Candida antarctica lipase B physically adsorbed within a macroporous poly(methyl methacrylate-co-butyl methacrylate) resin.Moreover,two derivatives of the β-peptoid oligomer were prepared: by acetylation and by grafting polycaprolactone. This last process was performed through ring opening polymerization of caprolactone from the β-peptoid pendant hydroxyl groups and afforded a brush copolymer. The products were blended with polycaprolactone to make films by solvent casting. The inclusion of the acyl derivatives of the β-peptoid to polycaprolactone affected the morphology of the film yielding micro- and nanostructured patterns.The obtained products showed biomedical applications. Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Garcia Liñares, Guadalupe Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina